2017
DOI: 10.1002/adfm.201704328
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding Directed Colloidal Self‐Assembly of Nanoparticles into 2D Crystals, Capsids, and Supracolloidal Assemblies

Abstract: Self-assembly of colloidal building blocks, like metal nanoparticles, is a rapidly progressing research area toward new functional materials. However, in-depth control of the colloidal self-assembly and especially hierarchical self-assembly is difficult due to challenges in controlling the size dispersities, shape/morphology, directionalities, and aggregation tendencies. Using either polydispersed or narrow-size dispersed nanoparticles, considerable progress has been achieved over the past few years. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 101 publications
1
60
0
Order By: Relevance
“…Figure d (Supporting Information, Video S4) show the TEM tomography reconstruction of GNR@Au 250 (Figure e shows the graphical representation of the same). Absence of any specific morphology in this case, even on completion of the reaction, can be due to the fact that Au 250 has to be partially deprotonated to facilitate water dispersibility . As a result, not all of the ligands are involved in H‐bonding, which decreases the packing density.…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…Figure d (Supporting Information, Video S4) show the TEM tomography reconstruction of GNR@Au 250 (Figure e shows the graphical representation of the same). Absence of any specific morphology in this case, even on completion of the reaction, can be due to the fact that Au 250 has to be partially deprotonated to facilitate water dispersibility . As a result, not all of the ligands are involved in H‐bonding, which decreases the packing density.…”
Section: Figurementioning
confidence: 98%
“…Recent reports of inter‐nanocluster reactions and isomorphous transformations have expanded the scope of their science. Moreover, it has been recently shown that by tuning the inter‐nanocluster H‐bonding, free‐standing 2D nanosheets and capsids with monolayer thick shells can be achieved using p MBA‐protected gold nanoclusters . On the other hand, noble metal nanoparticles, especially gold nanorods (GNRs), owing to their anisotropic surface plasmonic excitations and extreme sensitivity to chemical environments have been one of the most intensely researched nanosystems.…”
Section: Figurementioning
confidence: 99%
“…Absence of any specific morphology in this case, even on completion of the reaction, can be due to the fact that Au 250 has to be partially deprotonated to facilitate water dispersibility. [6,7] As aresult, not all of the ligands are involved in H-bonding, which decreases the packing density.S imilar structures have been obtained on treating GNRs with Au 102 (Supporting Information, Figure S10). Thus,i rrespective of the solvent this approach can be useful to condense any noble metal nanocluster,p rotected by hydrogen-bond-forming ligand on GNRs,which act as the nucleating sites.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Figure 3d (Supporting Information, Video S4) show the TEM tomography reconstruction of GNR@Au 250 (Figure 3e shows the graphical representation of the same). [6,7] As aresult, not all of the ligands are involved in H-bonding, which decreases the packing density.S imilar structures have been obtained on treating GNRs with Au 102 (Supporting Information, Figure S10). [6,7] As aresult, not all of the ligands are involved in H-bonding, which decreases the packing density.S imilar structures have been obtained on treating GNRs with Au 102 (Supporting Information, Figure S10).…”
mentioning
confidence: 99%
See 1 more Smart Citation